2017
DOI: 10.1155/2017/8698759
|View full text |Cite
|
Sign up to set email alerts
|

The Sulphate Effect on Lijiaxia Concrete Dam (China) Gallery

Abstract: The concrete degradation is one of the most serious problems for a dam construct during the normal operation, which determines the dam service life. Hence, it is very important to reduce the extent of the dam concrete degradation for the safety of the dam normal operation. Here, Lijiaxia hydroelectric station is taken as an example, and a comprehensive method to assess the sulphate effect on dam gallery is proposed. Eleven samples in total were taken from three difference locations by the drill bore. The micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Subsequent model experimental analysis showed that the erosion of tunnel-lining concrete by sulfates is the main cause of cracking and spalling of tunnel linings [ 7 ]. A similar situation occurred at Bapanxia Dam [ 8 ] and Lijiaxia Dam [ 9 ] in the northwestern region. Sulfate minerals in the underlying rock and soil bodies came in contact with the concrete via groundwater transport, causing severe damage to the concrete structure in the projects.…”
Section: Introductionsupporting
confidence: 56%
“…Subsequent model experimental analysis showed that the erosion of tunnel-lining concrete by sulfates is the main cause of cracking and spalling of tunnel linings [ 7 ]. A similar situation occurred at Bapanxia Dam [ 8 ] and Lijiaxia Dam [ 9 ] in the northwestern region. Sulfate minerals in the underlying rock and soil bodies came in contact with the concrete via groundwater transport, causing severe damage to the concrete structure in the projects.…”
Section: Introductionsupporting
confidence: 56%
“…In another study of civil dam related problems, the comprehensive evaluation method by using XRF, XRD, SEM, and EDS was applied to investigate the mechanism of the concrete degradation [4]. This is supported by the study of Silva et al, where it explains that microscopy is the only technique capable to clearly identify the features associated with DEF in concrete [5].…”
Section: Introductionmentioning
confidence: 93%